Micromorphological analysis of activity areas sealed by Vesuvius' Avellino eruption : the early Bronze Age village of Afragola in Southern Italy - Matarazzo, Tiziana (Archaeopress Publishing Ltd, 2015)
The remarkable preservation of the early Bronze Age village of Afragola on the Campania Plain of Southern Italy is unmatched in Europe. The site was buried under nearly a meter of volcanic ash deposited by the Avellino eruption of Vesuvius ca. 3945+10 cal. BP. The site boasts a large number of well-preserved structures, built features and organic materials and thus provides a laboratory-type setting in which to investigate variability in artifact distribution and activity areas across a single village. This research utilizes micromorphological analysis of thin sections of undisturbed sediment collected at the site to understand how people used living spaces, organized daily activities and, when possible, to connect village life to broad issues related to the emergence of social complexity on the Campanian Plain